PENGARUH BLANCHING NATRIUM METABISULFIT (NA2S2O5) TERHADAP SIFAT FISIK DAN ORGANOLEPTIK MANISAN KERING BUAH SEMU JAMBU METE (ANACARDIUM OCCIDENTALE, L) - Novian Wely Asmoro (Jurnal Ilmiah Teknosains, 2017)
The Aim of this research was to study the effect of the Na2S2O5 (Na-Metabisulphite) concentration and the time of blanching in the process of making candied dried fruit cashew to physical and organoleptic properties. The experimental design used is completely randomized design with two treatments and two replications factors. The length of time (T) with 3 levels of treatment, namely: T1 = 5 minutes T2 = 10 minutes, T3 = 15 minutes and the concentration of Na-Metabisulphite (K) with 4 levels of treatment; K1 = 0% (control), K2 = 0.05 %, K3 = 0.1% and K4= 0.15%. Analysis of the products include the measurement of water content, texture and organoleptic test (aroma, flavor, color, texture, and overall). The results of the analysis of water content in products an average of 11%. The longer time of blanching caused the texture of dried candied cashew increased. The higher concentration of Na-Metabisulphite in the blanching caused the value of texture decrease. Blanching treatment for 10 and 15 minutes using 0.05% Na-Metabisulphite has the overall organoleptic acceptance with the highest score of 3.6 means that the product is preferred by panelist.Keywords: candied dried fruit, cashew, Na-Metabisulphite, blanching